Analysis of Probiotic Role in Non-Alcoholic Fatty Liver Disease (NAFLD) Management: A Meta-Analysis - Wulandari, Jesika; Vidi Orba Busro (HM Publisher, 2024)
Background: Non-alcoholic fatty liver disease (NAFLD) is an increasing global health problem. Probiotics have emerged as a potential therapy for NAFLD, but evidence for their efficacy remains mixed. This meta-analysis aims to evaluate the effectiveness of probiotics in the management of NAFLD. Methods: A comprehensive literature search was performed on PubMed, Embase, Cochrane Library, and Web of Science databases until December 2023. Randomized controlled trials (RCTs) evaluating the effects of probiotics in NAFLD patients were included. The main outcomes evaluated were changes in liver enzymes (ALT, AST), insulin resistance index (HOMA-IR), and hepatic steatosis score. Meta-analysis was performed using a random effects model, and heterogeneity was assessed using the I² statistic. Results: Twenty-five RCTs involving 1845 patients met inclusion criteria. Meta-analysis showed that probiotics significantly reduced ALT (MD -8.45; 95% CI -12.67 to -4.23; p<0.0001) and AST (MD -6.89; 95% CI -10.11 to -3.67; p<0.0001) levels compared with placebo. Significant reductions were also observed in HOMA-IR (MD -0.68; 95% CI -1.02 to -0.34; p<0.0001) and hepatic steatosis scores (SMD -0.45; 95% CI -0.71 to -0.19; p=0.0008). Subgroup analysis showed that the effects of probiotics were more pronounced in patients with NAFLD non-alcoholic steatohepatitis (NASH) and those receiving multi-strain probiotics. Conclusion: This meta-analysis provides strong evidence that probiotics have beneficial effects on biochemical and imaging parameters in NAFLD patients. Probiotics may be considered as an adjunct therapy for NAFLD, especially in patients with NASH. However, more research is needed to determine the optimal probiotic strain, dosage, and duration of treatment.